Exploring the relationship between environmental factors and Covid-19 transmission in Selangor, Malaysia - Abd Ghani, N.; Che Dom, Nazri; Dapari, R.; Agyemang-Badu, S.Y. (Faculty of Medicine, University of Malaya, 2023)
The transmission and severity of Coronavirus Disease 2019 (COVID-19) are related to environmental factors such as temperature and humidity. The aim of this study is to investigate the association between daily reported COVID-19 cases and environmental variables. In this study, we used data from October 2020 to October 2021. We used a Generalised Additive Model (GAM) to examine the short-term relationship between COVID-19 and environmental variables in Selangor, Malaysia, using daily meteorological components and daily confirmed COVID-19 cases. We discovered a significant inverse relationship between daily confirmed COVID-19 cases and mean temperature (Tave), relative humidity, wind speed, rainfall, and wind effect index (K), while temperature-humidity index (THI) was significantly associated with an increase in daily confirmed COVID-19 cases. The results of this study provide important insights into the impact that environmental factors may have on the transmission of COVID-19 and should be considered in the development of public health interventions in Selangor, Malaysia.